Influence of bank lending to the government on private sector credit in Kenya: A fiscal deficit specification - Steve Makambi; Reuben Muhindi; Gillian Nduku (Kenya Bankers Association (KBA), 2017)
This study investigated the nexus of domestic bank lending to the Kenyan Government and Private sector credit taking into consideration the fiscal deficit environment characteristic of government debt accumulation. The main innovation of the study was to investigate the extent to which government borrowing crowds out(in) private sector credit after consideration of changes in fiscal regimes from 1966 to 2014. Two fiscal policy regimes are identified. Fiscal regime is defined as "active" if domestic public debt to GDP ratio increases in response to temporary rise in government expenditure. Fiscal policy regime is defined as "passive" if the government does not use domestic borrowing to finance unplanned expenditure. The investigations involved two major steps. Firstly, Markov switching model was used to identify fiscal policy regimes. Second, ARDL bound testing model was fitted and estimated to analyze the long run and short run effect of key variables on domestic private sector credit and the possible effect of regime changes on private sector credit. It was established that fiscal policy regime changes in Kenya were triggered by economic shocks and policy changes over the study period. The study also established that fiscal policy regimes are significant in explaining the relationship government debt-private sector credit. There was evidence that persistence increase in government debt crowds out private sector credit. The paper recommends prudential management of fiscal policy whic is core in managing government domestic borrowing.
Keywords: 330; government domestic borrowing; private sector credit; crowding out and fiscal policy regimes